Ameliorating effects of antioxidative compounds from four plant extracts in experimental models of diabetes - Dinić Svetlana; Uskoković Aleksandra; Mihailović Mirjana; Grdović Nevena; Arambašić Jelena; Marković Jelena; Poznanović Goran; Vidaković Melita (Journal of the Serbian Chemical Society, 2013)
Given that oxidative stress plays a major role in pancreatic β-cell dysfunction and ultimate destruction, as well as in different complications of diabetes, therapy with antioxidants has assumed an important place in diabetes management. The relatively limited effects of established antioxidant compounds have stimulated efforts to develop new therapeutic strategies, e.g. to increase the endogenous antioxidant defenses through pharmacological modulation of key antioxidant enzymes. Plant extracts are gaining popularity in treating diabetes because many substances synthesized by higher plants and fungi possess antioxidant activities and can prevent or protect tissues against the damaging effects of free radicals. This review summarizes experimental models of diabetes and possible mechanisms that lie behind the antioxidative effects of α-lipoic acid (LA), a powerful antioxidant and compound that stimulates cellular glucose uptake, as well as of plant extracts from sweet chestnut (Castanea sativa), edible mushroom (Lactarius deterrimus) and natural products containing β-glucans in the treatment of diabetes. Their roles in preventing pancreatic β-cell death and in ameliorating the effects of severe diabetic complications are discussed. [Projekat Ministarstva nauke Republike Srbije, br. 173020]